SPME/GC-MS characterization of volatile compounds of Chinese traditional-chopped pepper during fermentation - Jingjing Wang; Rongrong Wang; Qian Xiao; Chengguo Liu; Fangming Deng; Hui Zhou (International Journal of Food Properties, 2019)
Fermented-chopped pepper is a traditional-fermented vegetable in China. Chopped pepper is generally made with pepper, garlic, and ginger. In present study, the volatile compounds, obtained from chopped peppers during spontaneous fermentation, were analyzed by solid-phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS). One hundred and forty volatile compounds were identified by solvent-assisted flavor evaporation, including 42 hydrocarbons, 34 esters, 16 alcohols, 21 aldehydes, 8 acids, 4 ketones, 4 ethers, and 9 other compounds. Alcohols, esters, and ketones were the dominant volatile fractions. The terpenes were found to be the main contributors to chopped pepper samples. It is important to note that among terpenes, such as β-phellandrene, α-curcumene, elemene, geraniol and nerolidol may originated from ginger. In addition, diallyl disulfide and diallyl sulfide, the two major sulfur components, may originated from garlic volatile oils. The results indicated that the ginger and garlic as raw materials played an important role in the flavor of chopped pepper. The contents of esters significantly increased during the fermentation process, the ethyl palmitate and ethyl linoleate were the main esters. The content of β-ionone as an degradation compound of carotenoids increased significantly with the fermentation period. Principal component analysis (PCA) was applied to discriminate the fermented-chopped peppers samples according to different times, and the fermented-chopped pepper samples were clearly differentiated on PCA plots. The fermentation stage was mainly affected by esters, alcohols, aldehydes and terpenes.